Variations on Exposure Therapy: Best Practices for Managing Public Speaking Anxiety in the Online Communication Classroom - Sarah K. Chorley (Central States Communication Association, 2021)
Exposure and response prevention (ERP) therapy techniques offer unique opportunities for comprehensive management of public speaking anxiety in the online public speaking classroom beyond exposure to only the speech-giving act itself. This best practices article outlines nontraditional strategies for incorporating ERP practices in a distance-learning setting.